Uma plataforma para construção e uso de Arquiteturas Pedagógicas para aprendizagem de LIBRAS - Reinoso, Luiz Fernando (2016)
Pedagogical architectures are structures especially elaborated to support learning. A pedagogical architecture (AP) is designed with specific goals in mind (learning - what to learn?), Activities (what to do?), Methods (how?) and digital resources (resources that the learner can use) to support the development of the activities foreseen in the AP. Virtual learning spaces evolve into adjustable structures where learning can be shaped and enhanced. This paper discusses the construction of a platform for the creation and use of pedagogical architectures for learning LIBRAS, which is useful for apprentices training as interpreters in translation and interpretation of LIBRAS signs. The platform called Pedagogic Architectures Builder (CAP) enables the teacher to develop instrumented pedagogical architectures with several digital resources. APs created in CAP allow learners to perform both collaborative and individual activities. This paper uses concepts proposed in the MOrFEU project (Multi-Organizer Flexible of Virtual Spaces) about software development, pedagogical architectures and flexible environments for learning.